The Use of BrownAlgae Laminaria Saccharinain Iodine Enriched Products Aimed at PreventingIodine Deficiency - Shokina, Yulia; Kuchina, Yulia; Savkina, Ksenya; Novozhilova, Elena; Tatcienko, Katya; Shokin, Grigoriy (KnE Life Sciences, 2022)
The high content of iodine in dried algae has allowed it to be used as a physiologically functional food ingredient in the technology of fortified foods, which can help prevent iodine deficiency. The aim of this research was to develop a technology for food products enriched with iodine (Italian crispbreads), as well as fermented dairy products (thick and drinking yoghurts with various fruit fillings). The brown algae Laminaria saccharina, which originates from the islandFrøya (in Norway), was used to enrich the products with iodine. This algaewas grown on the farms of the company ”Energy Solutions AS” and was dried by various methods of low-temperature drying (heat pump at a temperature of minus 10 ∘C, drying in 1-3 layers; vacuum freeze drying with pre-storage at a temperature of minus 8 ∘C; and pre-freezing and storing at a temperature of minus 25 ∘C for 2-6 days). The chemical composition of the algae was studied. The findings showed that the modes of pretreatment of algae and the method of cold drying did not influence the following indicators (in % of the total mass of dried algae): the mass fraction of water (6.00±0.50% to 6.93±0.50%),ash (46.40-50.14%), andsodium chloride (31.00±1.75%). The above technological factors substantially affected the content of protein and iodine in the dried algae. Thus, the mass fraction of protein varied from 5.88% to 12.35% per total mass, and iodine varied from 0.367% to 0.522% in terms of dry matter. The optimal dosage of dried algae for adding to raw material was calculated (which provided anabove-stated iodine content of % of the recommended level of adequate consumption in 100g of the developed products): from 66% in crispbreads to 88% in fermented dairy products. All new products provided a high level of organoleptic evaluation. Keywords: brown algae, Laminaria saccharina, iodine, functionalproduct, crispbreads, drinking yoghurts, thick yoghurts